The Securitisation of cyberspace in South Africa : the tension between national security and civil liberties continues - Henwood, Roland David (University of Pretoria, 2018)
The concepts of national security and civil liberties have had a conflictual relationship throughout the history of human societies. Most societies have always strived to create a form of government that will maximise the security of individuals within the society while allowing each member to pursue their goals without encroaching on the rights and lives of others. This tense relationship between the two concepts came to be heightened by modern developments such as technology, mass migration and transnational terrorism. In particular, the development of cyberspace as technology advanced in the 20th century had a profound impact on the concepts of national security and civil liberties across the global political landscape, as states’ critical information infrastructures and private businesses have increasingly come to rely on cyber systems. Cyberspace, particularly with the arrival of the Internet in the late 1980s, created a virtual space for all members of society to interact and conduct social, political and business activities within and across borders. While this has had a positive impact in terms of economic and other opportunities for most people, it has also provided an innovative way for criminals and other actors to conduct illegal activities, with potential destructive consequences on businesses and state institutions as cyberspace proved to be plagued by security vulnerabilities. The overall response by most states to the potential national security threats posed by cyberspace has been the securitisation of the cyberspace domain, which has come to have negative implications on citizens’ civil liberties. Since 2010, South Africa has also gradually been implementing and drafting cybersecurity policies that have followed the typical securitisation trajectory. This study analyses the securitisation of cyberspace in South Africa. The research will contextualise the concepts of national security and civil liberties in relation to cybersecurity. The study will also examine the development of cybersecurity in South Africa and how it has impacted on the civil liberties of citizens and the country’s national security. In highlighting the various cyberattacks and consequences suffered in the country, this study will analyse the cyber-securitisation processes in South Africa, how it has affected civil liberties, how national security and civil liberties in South Africa can be balanced through cybersecurity, and whether securitisation of cyberspace in South Africa is necessary or not.